Literasi Kewirausahaan Dalam Membentuk Jiwa Wirausaha Mahasiswa Pendidikan Akuntansi Angkatan 2022 - Utami, Sri; Nurjannah, Nurjannah; Subur, Hikmayani (Jurnal Liabilitas, 2025)
Abstract - This research explores the role of entrepreneurial literacy in shaping the entrepreneurial spirit of Accounting Education students class of 2022 at State University of Makassar. Employing a descriptive qualitative approach with in-depth interviews and participatory observation techniques involving 14 informants selected through purposive sampling. Research findings indicate that entrepreneurial literacy contributes significantly to transforming students' mindset from job seekers to job creators. The cognitive dimension of entrepreneurial literacy manifests through mastery of business opportunity identification concepts, risk management, and sustainable business strategies. Affectively, changes occur in proactive attitudes, uncertainty tolerance, and innovation orientation. The psychomotor dimension is reflected in applicative capabilities for formulating business plans and implementing micro-enterprises. Nevertheless, gaps remain between theoretical competence and practical implementation requiring strengthening through direct experience. Integration of formal learning and experiential learning becomes key to optimizing entrepreneurial spirit formation that adapts to digital economic paradigm changes.